A genetically modified tobacco mosaic virus that can produce gold nanoparticles from a metal salt precursor. - Love, Andrew J.; Makarov, Valentine V.; Sinitsyna, Olga V.; Shaw, Jane; Yaminsky, Igor V.; Kalinina, Natalia O.; Taliansky, Michael (Frontiers in Plant Science, 2015)
We genetically modified tobacco mosaic virus (TMV) to surface display a characterized peptide with potent metal ion binding and reducing capacity (MBP TMV), and demonstrate that unlike wild type (WT) TMV, this construct can lead to the formation of discrete 10-40 nm gold nanoparticles when mixed with 3 mM potassium tetrachloroaurate. Using a variety of analytical physicochemical approaches it was found that these nanoparticles were crystalline in nature and stable. Given that the MBP TMV can produce metal nanomaterials in the absence of chemical reductants, it may have utility in the green production of metal nanomaterials.